1997
DOI: 10.1046/j.1365-2133.1997.17821869.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of psoriasis after syngeneic bone marrow transplant from psoriatic donor: further evidence for adoptive autoimmunity

Abstract: Transfer of donor immunity has been demonstrated in animal models of both allogeneic and syngeneic bone marrow transplantation (BMT). Clinical case reports have suggested that human autoimmune disease may be similarly transferred. However, it is difficult to completely exclude autoimmune phenomena associated with graft-versus-host disease (GVHD) as previously reported cases are of allogeneic BMT. In addition, the onset of autoimmunity has been distantly related to the timing of the transplant, perhaps because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 13 publications
1
60
0
1
Order By: Relevance
“…On the other hand, patients developing psoriasis after a syngeneic BMT from a psoriatic donor have been reported [15,16]. Experimental study in animal models has demonstrated that various autoimmune diseases can be transferred to healthy animals by BMT after total body irradiation [17].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, patients developing psoriasis after a syngeneic BMT from a psoriatic donor have been reported [15,16]. Experimental study in animal models has demonstrated that various autoimmune diseases can be transferred to healthy animals by BMT after total body irradiation [17].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence includes identification of clonal populations of T cells in diseased skin (2)(3)(4) and reversal of psoriasiform epidermal hyperplasia as well as other pathologic alterations by T celltargeted therapeutics. Also, psoriasis has erupted as a new disease in recipients of bone marrow transplants from psoriasis donors (5). In experimental xenograft models, ''normal'' skin of psoriasis patients has been converted to psoriasis by injection of superantigen-activated T cells (6), and spontaneous expansion of skin-resident T cells has produced psoriasis (7).…”
mentioning
confidence: 99%
“…This process initiates a pseudo-autoimmune reaction responsible for the psoriasiform outcome (Prinz et al, 1991;Leung et al, 1995;Valdimarsson et al, 2009). Interestingly, psoriasis was shown to be transferrable when the bone marrow of an affected individual was transplanted into a previously unaffected recipient (Snowden & Heaton, 1997). Conversely, psoriasis in a previously affected individual was completely cured after bone marrow ablation prior to transplant (Eedy et al, 1990).…”
Section: T Cell Transfer Modelsmentioning
confidence: 99%